The Relationship Between Social Cognition and Loneliness in Gifted Underachievers: The Mediating Role of Rejection Sensitivity - Saco, Victoria; Lucía Gómez, Carlos (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to examine the relationship between social cognition and loneliness in gifted underachievers, with a specific focus on the mediating role of rejection sensitivity. A descriptive correlational design was employed with a sample of 399 gifted underachieving adolescents from Argentina, selected according to Morgan and Krejcie’s (1970) sample size table. Standardized tools were used to assess social cognition, rejection sensitivity, and loneliness. Data analysis was conducted using SPSS-27 and AMOS-21. Pearson correlation was used to evaluate bivariate relationships between variables, and Structural Equation Modeling (SEM) was applied to test the proposed mediational model. Fit indices, including χ², RMSEA, GFI, CFI, and TLI, were reported to evaluate model adequacy. Results indicated that social cognition was significantly and negatively correlated with both rejection sensitivity (r = –.43, p < .01) and loneliness (r = –.39, p < .01). Rejection sensitivity showed a significant positive correlation with loneliness (r = .58, p < .01). SEM analysis confirmed the mediating role of rejection sensitivity in the relationship between social cognition and loneliness. The indirect path from social cognition to loneliness via rejection sensitivity was significant (β = –.28, p < .001), and the total effect of social cognition on loneliness was substantial (β = –.49, p < .001). Model fit indices indicated a good fit (χ²/df = 2.22, CFI = 0.96, RMSEA = 0.054). These findings suggest that deficits in social cognition contribute to heightened feelings of loneliness in gifted underachievers, primarily through increased sensitivity to perceived rejection. Interventions aimed at reducing rejection sensitivity may mitigate the impact of social cognitive difficulties on emotional well-being in this vulnerable group.